High Resolution Spectroscopy of CF3Br by Diode Laser in the Frequency Range 1070–1090 cm−1. Issue 1 (1988) - de Bekker, R.; Ebben, M.; Snels, M.; Stolte, S.
Abstract : The IR absorption spectra of gaseous CF3 Br expanded in a molecular jet have been recorded with a linewidth of about 0.002 cm −1 . The rotational K -structure of the ν 1 fundamental has been resolved and the molecular constants Δ B and Δ A have been determined with an accuracy better than 5 x 10 −6 cm −1 . Spectral features belonging to theν 6 - andν 3 -hotbands have been identified. For CF3 B 79 r (CF3 B 81 r ) improved values of the vibrational origins for the fundamental ν 1 = 1084.768(2) cm −1 (1084.520(2) cm −1 ) and for its hotbandsν 3 + ν 1 ← ν 3 = 1081.709(80) cm −1 (1081.065(40) cm −1 ) andν 6 + ν 1 ← ν 6 = 1083.533(4) cm -1 (1083.288(4) cm -1 ) have been determined.